Association between life's essential 8 and colorectal cancer: A population-based study - Ma, Xiaohan; Zhang, Xiaofei; Wu, Fasheng; Chen, Sheng; Peng, Jing; Lan, Xuan; Zhang, Xinyue; Hou, Encun (Medicine (Baltimore), 2025)
Colorectal cancer (CRC) is closely linked to cardiovascular disease. This study investigates the relationship between life's essential 8 (LE8), a recent cardiovascular health metric, and CRC prevalence in US adults. Data from the 2011 to 2018 National Health and Nutrition Examination Survey were used in this study. LE8 was classified into high, moderate, and low levels. The association between LE8 and CRC was assessed using weighted logistic regression, restricted cubic splines, and subgroup analyses. After adjusting for potential confounders, higher LE8 scores were linked to a lower prevalence of CRC. Individuals with the highest LE8 scores had an 81% reduced risk of CRC compared to those with the lowest scores (odds ratio = 0.19; 95% confidence interval: 0.04-0.88, P = .03). Restricted cubic splines analyses revealed a negative correlation between CRC risk and LE8 scores, showing a linear decline as LE8 scores increased (P for non-linearity > .05). LE8 was inversely associated with CRC prevalence in a linear manner. Encouraging adherence to optimal cardiovascular health may help reduce CRC burden.